Striving for excellence in a little red dot: Exploring the evolution of oral and maxillofacial surgery training and practice in Singapore - Bernadette Quah; Chee Weng Yong; Asher Ah Tong Lim; Raymond Chung Wen Wong; Sung-Kiang Chuang (Journal of Dental Sciences)
Oral and maxillofacial surgery (OMS) is a field that straddles knowledge and clinical experience from both medical and dental specialties. In the small island nation of Singapore, the rapidly and constantly changing needs of its diverse and aging population, as well as changes in the mindsets of both students and educators have led to many developments in the local OMS program. Tied to the only dental school in the country, the curriculum of the training program has kept up with the changes in the demographics and attitudes of the local patient pool, which comprises a multicultural population with both traditional and modern mindsets. Since its inception, the training program has also shifted away from the traditional apprenticeship model of surgical specialties to include more integrated and modular learning with a heavy emphasis on evidence-based medicine, simulation training workshops, and more focus on digital planning and other technological advancements. This review explores the current scope of training and practice in the Singapore landscape, and how it has evolved and been tailored to meet the needs of its patients and future clinicians.